2018
DOI: 10.5958/0974-0279.2018.00044.7
|View full text |Cite
|
Sign up to set email alerts
|

Public expenditure on agriculture and economic growth: a case study of Meghalaya

Abstract: This paper assesses the impact of government expenditure on agriculture and allied activities on economic growth (GSDP) in Meghalaya during the period 1984-85 to 2013-14. We find a significant positive impact of agricultural expenditure on crop husbandry on GSDP growth. On the other hand, the impact of public expenditure on forestry, dairy and irrigation is found out to be negative. These findings conclude that although crop husbandry happens to have a significant positive impact of economic growth, the need f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…Similarly, literature provides evidence that the sensible usage of public spending on agriculture has the reasonable capacity to speed up agronomic progress and perk up its productivity (Dkhar & Kumar, 2018). Likewise, Salim and Islam (2010) detailed that agricultural R&D expands the farming output in the long run.…”
mentioning
confidence: 99%
“…Similarly, literature provides evidence that the sensible usage of public spending on agriculture has the reasonable capacity to speed up agronomic progress and perk up its productivity (Dkhar & Kumar, 2018). Likewise, Salim and Islam (2010) detailed that agricultural R&D expands the farming output in the long run.…”
mentioning
confidence: 99%
“…Government Agricultural Expenditure (GEA) are transfer made from the government to economic agents (producers and input suppliers), for general support for agricultural infrastructure, R&D and extension services, marketing, storage, or inspection facilities, among others, and administrative costs (that cost linked to policy formulation and coordination and running costs of ministries and other public entities (Pernechele et al, 2021). Based on the Keynes postulation and previous studies (Dkhar and De, 2018;Tijani et al, 2015;Shuaib et al, 2015), this study posits that government agricultural expenditure would have a positive effect of economic growth. Domestic Investment (DI) is an essential component that can enable economic growth (Overseas Development Institute, ODI, 2016).…”
Section: Description Of Variablementioning
confidence: 98%
“…Similarly, Chu et al, (2020), Amusa and Oyinola (2019), Ndubuisi (2018), Garoma and Bersisa (2018), Selvanathan et al, (2021), Arestis et al, (2021), Lupu et al, (2018), Mazorodze (2018) demonstrated using various analytical techniques that effect of government expenditure on growth depends on the sector recipient or functional component of government expenditure. In relation to government agricultural expenditure and economic growth Shuaib et al (2015), Ebenezer et al, (2019), and Dkhar and De (2018) showed that government expenditure on agriculture does influence agricultural productivity and economic growth positively in Nigeria, South Africa and Russia, respectively. Furthermore, evidence from empirical literature further show that several macroeconomic factors besides government expenditure influence the level of growth in an economy, the extent of their influences however differs across countries, regions, and income groups.…”
Section: Government Expenditure and Economic Growth: Empiricsmentioning
confidence: 99%
“…According to Oriakhi and Arodoye [ 14 ], the agricultural sector is primarily driven by their contributions, which are significant in long-term economic and capital growth. It creates employment and investment opportunities in rural areas and helps urban areas [ 15 ]. In the case of China, Fig.…”
Section: Introductionmentioning
confidence: 99%